Reviu Desain Struktur Bawah Bangunan Gedung: Studi Kasus Pengecekan Kekuatan Pondasi Tapak Sekolah Dasar Negeri (SDN) 12 Muntei, Mentawai - Fitria, Winda; Misriani, Merley; Syofyan, Elvi Roza (FROPIL (Forum Profesional Teknik Sipil), 2023)
Muntei is one of the villages in South Siberut, Mentawai Island Regency. The Mentawai Island located in West Sumatera and are outside the territory of the island of Sumatera, including one of the outermost islands in this Province. Mentawai is one of the areas in West Sumatera that is frequently shaken by earthquake. So, the implementation of earthquake resistant building standars is an important factor that must be considered in efforts to reduce disaster risk, considering that West Sumatera is one of the areas with a high earthquake risk. The implementation of earthquake resistant building standards should have started during the planning process. As one of the outermost province Mentawai is also lagging behind in infrastructure development, so sustainable development needs to be carried out to make Mentawai come out of being behind compare to other district in the West Sumatera. The review design of the site foundation of the SDN 12 Muntei school building aims to ensure the carrying capacity of the foundation. To obtain maximum axial value of the building, modeling was carried out using the sap2000 application. From the modeling and data analysis can be concluded that the foundation does not meet the requirements and is unable to carry the maximum load of the building. The allowable capacity of foundation permit for the SDN 12 Muntei is 12.96 Tonenes, while the maximum load on the building is 34.57 tonnes. The result of this analysis show that the foundation is not good and must be repaired.